Indigenous students’ attitudes towards learning english through a virtual program: a study in a colombian public university (2010)
This article reports an exploratory study carried out at a public university in Bogotá, Colombia, with two indigenous students who took a level I virtual English-course during the second term of 2008 and the first term of 2009. The aim was to analyse their attitudes towards the learning of English through the virtual modality. Interviews, observations and questionnaires were used for data collection. It was found that indigenous students felt frustrated taking a virtual English course, and that their motivation as regards the learning of this language is very low. Thus, they need to be motivated and guided along the process. At the end, some recommendations for teaching or tutoring indigenous students, learning English virtually or any of the other modalities of the English program at the university were derived. En este artículo se reporta un estudio exploratorio que se llevó a cabo en una universidad pública en Bogotá, Colombia, con dos estudiantes indígenas que realizaron un curso virtual de inglés durante el segundo semestre del 2008 y el primero del 2009. El objetivo fue analizar sus actitudes frente al aprendizaje de inglés a través de la modalidad virtual. La recolección de datos se hizo mediante entrevistas, observaciones y cuestionarios. Se encontró que los estudiantes sienten frustración al tomar un curso de inglés virtual, por lo que su motivación hacia el aprendizaje de este idioma es muy baja. Por tal razón, deben ser motivados y guiados en el proceso. Al finalizar el estudio, se produjeron algunas recomendaciones para la enseñanza o la tutoría a estudiantes indígenas a través de ambientes virtuales o de cualquiera de las otras modalidades del programa de inglés en la universidad.